A Case for Deep Learning Through Online Oral Examinations: An Autoethnographical Exploration of a Change of Assessment Method - Turunen, Jaakko (Högre utbildning, 2023)
The Covid-19 pandemic made digital oral exams a necessity for most higher education courses in Sweden and elsewhere in the world. Yet, more reflection on oral examination could help understand their utility in contemporary higher education. This paper probes the relationship between learning habits and assessment through an autoethnographic exploration into oral examination in an intermediate quantitative methods class for social science students in Sweden. Drawing on theories on constructive alignment and deep learning, this article makes the case for oral examinations as facilitating deep(er) learning. At the same time, the article discusses the oral examination as a critical way to think about the formal assessment culture brought about by ever tightening teaching budgets and external audits.